Drowning lessons : stories - Selgin, Peter (Flannery O'Connor Award for Short Fiction., 2008)
"The stories in "Drowning Lessons" engage water's presence as both a vital and a potentially hazardous element in our lives. "You can touch water," says Peter Selgin, "you can taste it and feel its temperature, you can even hold it in your hands. Still it remains elusive, ill-defined, shaped only by what surrounds or contains it. With empathy and wit, Selgin introduces us to characters navigating the choppy waters of human relationships ... In all thirteen tales in "Drowning Lessons", Selgin exhibits a keen eye for the forces that push people toward - and sometimes beyond - their very human limits, forces as intrinsic, elemental, and elusive as the liquid that makes up two-thirds of their bodies. These stories remind us that of all bodies of water, none is deeper or more dangerous than our own"--Publisher's description